1993
DOI: 10.1002/chin.199308274
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: X‐Ray Crystal Structure of (.+‐.)‐Pandamarine (I), the Major Alkaloid of Pandanus amaryllifolius.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Pandamarine ( 1 , Scheme ) is an alkaloid that was isolated in 1992 by Byrne’s group from the leaves of the tropical plant Pandanus amaryllifolius . Pandamarilactone-1 ( 2 , Scheme ), was also isolated from the same plant one year later .…”
supporting
confidence: 87%
See 2 more Smart Citations
“…Pandamarine ( 1 , Scheme ) is an alkaloid that was isolated in 1992 by Byrne’s group from the leaves of the tropical plant Pandanus amaryllifolius . Pandamarilactone-1 ( 2 , Scheme ), was also isolated from the same plant one year later .…”
supporting
confidence: 87%
“…Biogenetically, the isolation team have proposed that pandamarine ( 1 ) might be the spiro- N,N -ketalization product of a symmetric bis -lactam ( 3 , Scheme ). , This proposal is consistent with the fact that pandamarine ( 1 ) occurs as a racemate. It was suggested that this possible biogenetic intermediate 3 might in turn be obtained from (2 S )-4-hydroxy-4-methylglutamic acid ( 4 , Scheme ) since this amino acid was found in a related species, P.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2-1 to fr. [2][3][4][5][6][7][8][9][10][11][12]. Fraction 2-6 (130 mg) was separated on a Sephadex LH-20 column eluted with chloroform-MeOH (1 : 1) chloroform to afford six fractions (fr.…”
Section: Experimental General Experimental Procedures High Resolutionmentioning
confidence: 99%
“…3) In addition, their antioxidant activity 4) and antihyperglycemic effects 5) have been reported. Various alkaloids have also been isolated form P. amaryllifolius, [6][7][8][9] and several studies have reported their isolation and structure. [10][11][12][13][14][15] Here, we report the isolation of a novel p-coumaroyl dimethyl malate (1) in addition to three known p-comaroyl malate derivatives (2)(3)(4) (Fig.…”
mentioning
confidence: 99%